2020
DOI: 10.1093/nar/gkaa556
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of intragenic CpG islands influences spatiotemporal host gene pre-mRNA processing

Abstract: Abstract Alternative splicing (AS) and alternative polyadenylation (APA) generate diverse transcripts in mammalian genomes during development and differentiation. Epigenetic marks such as trimethylation of histone H3 lysine 36 (H3K36me3) and DNA methylation play a role in generating transcriptome diversity. Intragenic CpG islands (iCGIs) and their corresponding host genes exhibit dynamic epigenetic and gene expression patterns during development and between diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…Similar polyadenylation site usage was also found when DNA methylation was perturbed at the iCGI within the NFATc1 locus, resulting in alternative NFATc1 isoforms. These locus specific effects have been detected genome-wide by a recent bioinformatic screen, emphasising that iCGI activity leads to premature transcription termination upstream of the iCGI, most likely through APA (Amante et al, 2020) (Figures 2B,D).…”
Section: Consequences On the Gene For Hosting An Active Intragenic Cgimentioning
confidence: 83%
See 3 more Smart Citations
“…Similar polyadenylation site usage was also found when DNA methylation was perturbed at the iCGI within the NFATc1 locus, resulting in alternative NFATc1 isoforms. These locus specific effects have been detected genome-wide by a recent bioinformatic screen, emphasising that iCGI activity leads to premature transcription termination upstream of the iCGI, most likely through APA (Amante et al, 2020) (Figures 2B,D).…”
Section: Consequences On the Gene For Hosting An Active Intragenic Cgimentioning
confidence: 83%
“…iCGIs are more likely to be DNA methylated (Figure 1C) and those lacking DNA methylation can exhibit bivalent chromatin signatures and when transcriptionally active, show transcription factor binding and the promoter mark, H3K4me3 (Lee et al, 2017;Amante et al, 2020;Choi et al, 2020). iCGIs can therefore exist in the same 'states' as promoter CGIs, albeit in different proportions.…”
Section: Cgis Are Promoters Independent Of Genomic Positionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our approach was downregulated genes with CGIs but is important to announce that DNMT3B overexpression also was related to the up-regulation of several genes. The methylation in intragenic CGIs 51 is related to cell differentiation 52 , 95 , active transcription, and enrichment of histone modifications such as H3K36me3 50 . We studied genes possibly related to the catalytic DNMT3B function, and a limitation of our study is that we can’t discriminate whether the change observed in all the deregulated genes is a catalytic or accessory function of DNMT3B 96 , we specifically tested the catalytic function in the 4 selected genes.…”
Section: Discussionmentioning
confidence: 99%